A kind of alkyl polyglucoside material with high temperature stability and preparation method thereof
The enzyme catalytic process achieves high polymerization degree and self-assembly of alkyl polyglucosides to form a hexagonal crystal system with π-π conjugation effect, solving the problems of insufficient thermal stability and poor mechanical properties of existing alkyl polyglucosides in high temperature environments, and achieving the effect of maintaining structural and functional stability at high temperatures. It is suitable for a variety of high-temperature application fields.
Patent Information
- Application Number
- CN202510020844.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-01
AI Technical Summary
The existing alkyl polyglucosides have insufficient thermal stability, poor mechanical properties and limited application range in high-temperature environments, which cannot meet the demand for high-temperature resistant materials in aerospace, electronic packaging and other fields.
Through the process of combining enzyme-catalyzed reverse hydrolysis and glycosyl transfer, high polymerization and self-assembly of alkyl glycosides are achieved, a spherical cage-like nanostructure is formed, and π-π conjugation is introduced between molecules to construct a graphene-like hexagonal crystal system.
The material maintains structural integrity and functional stability under a high temperature environment of 580-930°C, and the decomposition loss is significantly lower than that of traditional biological materials. It is suitable for aerospace, electronic packaging and high-temperature insulation coatings and other fields.
Smart Images

Figure CN119735822A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-performance biomaterials and heat-resistant functional materials, in particular to an alkyl polyglucoside material with high-temperature stability and a preparation method thereof. Background Art
[0002] Alkyl polyglucosides (APGs) are a class of nonionic surfactants formed by fatty alcohols and glucose connected by glycosidic bonds. They have an amphiphilic structure: the hydrophilic head comes from the glucose molecule, providing good hydrophilicity, while the hydrophobic tail is composed of fatty alcohol chains of different lengths (such as butyl, hexyl, octyl, etc.), giving it good hydrophobicity and self-assembly properties. Due to its natural origin, green environmental protection, and biodegradability, APGs are widely used in many fields. For example, in the field of daily chemicals, APGs are often used as cleaning agents and emulsifiers, and are used in detergents, cosmetics and other products; in the food industry, APGs can be used as food emulsifiers, meeting safety and non-toxic requirements; in the agricultural field, APGs are used in pesticide preparations and wetting agents to improve the dispersibility and permeability of drug efficacy; in addition, in industrial applications, APGs are used as oilfield additives, coating dispersants and textile printing and dyeing auxiliaries, showing good emulsification and solubilization properties.
[0003] Although APGs exhibit excellent emulsification properties and environmental friendliness under low and room temperature conditions, there are still obvious technical bottlenecks in high-temperature applications, which limits their wider industrial applications. First, insufficient thermal stability is the main problem facing traditional APGs. Existing low-molecular-weight alkyl glycosides are prone to decomposition under high temperature conditions, resulting in material structure damage and a sharp decline in performance, which cannot meet the needs of aerospace, electronic packaging and other fields for high-temperature resistant materials; secondly, unstable mechanical properties are also an important constraint. Traditional APGs have a loose structure and it is difficult to form a stable crystal structure, resulting in their mechanical strength and thermal properties unable to meet the requirements under extreme conditions; finally, limited application scope is also a bottleneck in the current technological development. The use scenarios of APGs are mainly concentrated in low and room temperature environments, and the leapfrog application development to high-temperature functional materials has not yet been achieved.
[0004] Therefore, how to improve the thermal stability and mechanical properties of APGs through molecular design and self-assembly strategies, and give them stability and functionality in high temperature environments, is a technical problem that needs to be solved urgently in the current field. The present invention addresses this key issue and breaks through the limitations of traditional APGs, and thus proposes an alkyl polyglucoside material with high temperature stability and a preparation method thereof to solve the above problems. Summary of the invention
[0005] 1. Technical issues to be solved
[0006] In view of the deficiencies in the prior art, the present invention provides an alkyl polyglucoside material with high temperature stability and a preparation method thereof, which has the advantages of high temperature stability and the like, and solves the problems of the existing alkyl polyglucoside such as insufficient thermal stability, poor mechanical properties and limited application range under high temperature environments.
[0007] (II) Technical solution
[0008] To achieve the above object, the present invention provides the following technical solution: a method for preparing an alkyl polyglucoside material with high temperature stability, comprising the following steps:
[0009] S1. Glycosylation reaction: prepare a glucose solution with a concentration of 0.5M to 2.0M, mix it with an equal volume of sodium phosphate buffer, then add 1.0mL to 3.0mL of a hydrophobic alcohol compound, stir well to form a uniform mixture, add a catalyst, and then add 0.01M to 0.05M cobalt chloride and 0.01M to 0.05M copper sulfate to preliminarily generate an alkyl glycoside monomer;
[0010] S2. Polymerization and self-assembly: The enzyme-catalyzed glycosyl transfer reaction further polymerizes the alkyl glycoside monomers to form a molecular structure in which the polysaccharide chain is combined with the alkyl chain. As the reaction proceeds, the molecules self-assemble under the action of the hydrophobic phase to form a nanoscale polymer framework with a cage-like structure.
[0011] S3, reaction termination and separation and purification: after the reaction is completed, 3 mL of methanol is added to terminate the enzyme catalytic reaction, and then the enzyme catalyst is removed by using a filter membrane, and the excess reaction solvent is removed by vacuum evaporation, and then three times the volume of methanol is added and stirred and filtered to remove unreacted glucose, and finally the reaction solution is separated from 10 times the volume of ethanol-hexane mixed solvent by liquid-liquid separation, the organic phase is recovered, and the solvent is removed by rotary evaporation to obtain the purified polymerized alkyl polyglucoside;
[0012] S4. Characterization of structure and performance: Infrared spectroscopy was used to detect the vibration peaks of the COC glycosidic bond and the alkyl chain. Nuclear magnetic resonance was used to determine the degree of polymerization and structural integrity of the material. The crystal structure of the material was further analyzed by X-ray diffraction and Raman spectroscopy to confirm the formation of a hexagonal crystal system with π-π conjugation. Thermal stability tests were performed using thermogravimetric analysis and differential scanning calorimetry. The results showed that the material can still maintain a stable structure and performance in a high temperature environment of 580–930°C.
[0013] Preferably, the glycosylation reaction in S1 is carried out at 50°C-120°C.
[0014] Preferably, the glycosylation reaction in S1 lasts for 60-240 hours.
[0015] Preferably, the hydrophobic alcohol compound in S1 is one of butanol, hexanol or octanol.
[0016] Preferably, the catalyst in S1 is 24U of α-glucosidase.
[0017] Preferably, the pH value of the sodium phosphate buffer is 6.5-7.5.
[0018] Preferably, the volume ratio of ethanol to hexane in the S3 ethanol-hexane mixed solvent is 1:1.
[0019] Preferably, the pore size of the filter membrane in S3 is 0.22 μm.
[0020] An alkyl polyglucoside material with high temperature stability is prepared by the preparation method of the alkyl polyglucoside material with high temperature stability.
[0021] (III) Beneficial effects
[0022] Compared with the prior art, the present invention provides an alkyl polyglucoside material with high temperature stability and a preparation method thereof, which has the following beneficial effects:
[0023] 1. The alkyl polyglucoside material with high temperature stability and the preparation method thereof realize the high polymerization degree and self-assembly of alkyl glycoside through a process combining enzyme-catalyzed reverse hydrolysis and glycosyl transfer. Different from the traditional APGs material, the present invention forms a cage-like nanostructure through molecular design and introduces π-π conjugation between molecules, thereby constructing a graphene-like hexagonal crystal system. This innovative structure effectively solves the problem that traditional APGs are easy to decompose and have unstable structure under high temperature conditions.
[0024] 2. The high-temperature stable alkyl polyglucoside material and its preparation method were tested by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) and found that the material still maintained structural integrity and functional stability in a high-temperature environment of 580-930°C, and the decomposition loss was significantly lower than that of traditional biomaterials. In addition, the lightweight properties of the material give it significant advantages in high-temperature applications, and it is particularly suitable for aerospace, electronic packaging, and high-temperature insulation coatings.
[0025] 3. The high-temperature stable alkyl polyglucoside material and its preparation method replace the traditional high-temperature and high-pressure chemical synthesis method with a mild enzyme catalysis process, avoiding the use of harmful reagents, reducing the risk of environmental pollution, and improving the selectivity of the reaction and the purity of the product, meeting the requirements of sustainable development.
[0026] 4. The alkyl polyglucoside material with high temperature stability and its preparation method were characterized by X-ray diffraction and Raman spectroscopy. It was found that the multilayer crystal structure in the material effectively improved its mechanical strength, overcoming the defects of traditional APGs materials such as loose structure and insufficient performance. This makes the material of the present invention still have stable physical and chemical properties under extreme conditions, significantly broadening its application field. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The figure is a schematic flow chart of a method for preparing an alkyl polyglucoside material with high temperature stability according to the present invention;
[0028] Figure 2 A schematic diagram of a qualitative analysis of butyl HP-LC determination of an alkyl polyglycoside of an alkyl polyglucoside material with high temperature stability according to the present invention;
[0029] Figure 3 It is a schematic diagram of the qualitative analysis of the hexyl HP-LC determination of the alkyl polymer glycoside of the alkyl polyglucoside material with high temperature stability of the present invention;
[0030] Figure 4 A schematic diagram of the qualitative analysis of the octyl HP-LC determination of the alkyl polymer glycoside of an alkyl polyglucoside material with high temperature stability of the present invention;
[0031] Figure 5 It is a schematic diagram of the heat resistance determination of butyl, hexyl and octyl polymerized glycosides of an alkyl polyglucoside material with high temperature stability of the present invention;
[0032] Figure 6 A schematic diagram of the molecular weight and apparent structure of butyl, hexyl and octyl polymerized glycosides of an alkyl polyglucoside material with high temperature stability of the present invention;
[0033] Figure 7 The figure is a schematic diagram of the chemical structure analysis of butyl, hexyl and octyl polymerized glycosides of an alkyl polyglucoside material with high temperature stability of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] See also Figure 1-7 , a method for preparing an alkyl polyglucoside material with high temperature stability, comprising the following steps:
[0036] S1. Glycosylation reaction: prepare a glucose solution with a concentration of 0.5M to 2.0M, mix it with an equal volume of sodium phosphate buffer, then add 1.0mL to 3.0mL of a hydrophobic alcohol compound, stir well to form a uniform mixture, add a catalyst, and then add 0.01M to 0.05M cobalt chloride and 0.01M to 0.05M copper sulfate to preliminarily generate an alkyl glycoside monomer;
[0037] S2. Polymerization and self-assembly: The enzyme-catalyzed glycosyl transfer reaction further polymerizes the alkyl glycoside monomers to form a molecular structure in which the polysaccharide chain is combined with the alkyl chain. As the reaction proceeds, the molecules self-assemble under the action of the hydrophobic phase to form a nanoscale polymer framework with a cage-like structure.
[0038] S3, reaction termination and separation and purification: after the reaction is completed, 3 mL of methanol is added to terminate the enzyme catalytic reaction, and then the enzyme catalyst is removed by using a filter membrane, and the excess reaction solvent is removed by vacuum evaporation, and then three times the volume of methanol is added and stirred and filtered to remove unreacted glucose, and finally the reaction solution is separated from 10 times the volume of ethanol-hexane mixed solvent by liquid-liquid separation, the organic phase is recovered, and the solvent is removed by rotary evaporation to obtain the purified polymerized alkyl polyglucoside;
[0039] S4. Characterization of structure and performance: Infrared spectroscopy was used to detect the vibration peaks of the COC glycosidic bond and the alkyl chain. Nuclear magnetic resonance was used to determine the degree of polymerization and structural integrity of the material. The crystal structure of the material was further analyzed by X-ray diffraction and Raman spectroscopy to confirm the formation of a hexagonal crystal system with π-π conjugation. Thermal stability tests were performed using thermogravimetric analysis and differential scanning calorimetry. The results showed that the material can still maintain a stable structure and performance in a high temperature environment of 580–930°C.
[0040] Preferably, the glycosylation reaction in S1 is carried out at 50°C-120°C.
[0041] Preferably, the glycosylation reaction in S1 lasts for 60-240 hours.
[0042] Preferably, the hydrophobic alcohol compound in S1 is one of butanol, hexanol or octanol.
[0043] Preferably, the catalyst in S1 is 24 U of α-glucosidase.
[0044] Preferably, the pH value of the sodium phosphate buffer is 6.5-7.5.
[0045] Preferably, the volume ratio of ethanol to hexane in S3 ethanol-hexane mixed solvent is 1:1.
[0046] Preferably, the pore size of the filter membrane in S3 is 0.22 μm.
[0047] A high-temperature stable alkyl polyglucoside material, which consists of a glucose unit as a hydrophilic head and an alkyl chain as a hydrophobic tail. It forms a unique cage-like nanostructure through molecular polymerization and self-assembly, and introduces π-π conjugation between molecules, thereby constructing a highly stable multilayer graphene hexagonal crystal system. This structure significantly enhances the thermal stability of the material, enabling it to maintain structural stability and functional integrity in a high-temperature environment of 580–930°C.
[0048] Example 1: 0.5 mmol of glucose was dissolved in 0.25 mL of sodium phosphate buffer at pH 6.5, 1 mL of butanol was added as a hydrophobic group source, and 24 U of α-glucosidase was added as a catalyst, and then 0.01 M of cobalt chloride and 0.02 M of copper sulfate were added. The reaction system was stirred continuously for 60 hours at 50 ° C to generate alkyl glycoside monomers and partial polymers. After the reaction was completed, 3 mL of methanol was added to terminate the reaction, and the enzyme catalyst was removed by filtration using a 0.22 μm filter membrane. The residual solvent was removed by rotary evaporation at 90 ° C and 25 mbar to obtain a preliminary purified APGs material. The reaction solution was separated from 10 times the volume of ethanol-hexane mixed solvent (1:1) by liquid-liquid separation, the organic phase was recovered, and the solvent was further removed by rotary evaporation to finally obtain purified polymeric APGs.
[0049] Example 2: 1.0 mmol of glucose was dissolved in 0.5 mL of sodium phosphate buffer at pH 7, 2 mL of octanol was added as a hydrophobic group source, and 24 U of α-glucosidase was added as a catalyst, and 0.03 M of cobalt chloride and 0.04 M of copper sulfate were added. The reaction system was stirred continuously for 120 hours at 75 ° C to generate alkyl glycoside monomers and partial polymers. After the reaction was completed, 3 mL of methanol was added to terminate the reaction, and the enzyme catalyst was removed by filtration using a 0.22 μm filter membrane. The residual solvent was removed by rotary evaporation at 90 ° C and 25 mbar to obtain a preliminary purified APGs material. The reaction solution was separated from 10 times the volume of ethanol-hexane mixed solvent (1:1) by liquid-liquid separation, the organic phase was recovered, and the solvent was further removed by rotary evaporation to finally obtain purified polymeric APGs.
[0050] Example 3: 2.0 mmol of glucose was dissolved in 0.75 mL of sodium phosphate buffer at pH 7.5, 3 mL of hexanol was added as a hydrophobic group source, and 24 U of α-glucosidase was added as a catalyst, and then 0.05 M of cobalt chloride and 0.03 M of copper sulfate were added. The reaction system was continuously stirred for 240 hours at 120°C to generate alkyl glycoside monomers and partial polymers. After the reaction was completed, 3 mL of methanol was added to terminate the reaction, and the enzyme catalyst was removed by filtration using a 0.22 μm filter membrane. The residual solvent was removed by rotary evaporation at 90°C and 25 mbar to obtain a preliminarily purified APGs material. The reaction solution was separated from 10 times the volume of ethanol-hexane mixed solvent (1:1) by liquid-liquid separation, the organic phase was recovered, and the solvent was further removed by rotary evaporation to finally obtain purified polymeric APGs.
[0051] Test Example 1: The purified APGs material obtained in the example was subjected to the following tests:
[0052] 1) Infrared spectroscopy (FTIR): The characteristic peak of COC glycosidic bond at 1100–1200 cm-1 was detected, confirming the formation of glycosidic bond;
[0053] 2) Nuclear magnetic resonance (1H-NMR): Multiple peaks of sugar ring hydrogen were detected in the range of 3.0–5.5 ppm. Combined with the alkyl chain signals of 0.8–2.5 ppm, the degree of polymerization of APGs was calculated to be about 11–25;
[0054] 3) X-ray diffraction (XRD): A significant diffraction peak appears at 2θ=26.5°, indicating that APGs forms a hexagonal crystal structure similar to graphene;
[0055] 4) Thermogravimetric analysis (TGA): The mass loss of the sample in the range of 580–930 °C was less than 5%, showing extremely high thermal stability.
[0056] Test Example 2: Application test of APGs material in high temperature coating:
[0057] The APGs material prepared in the embodiment was dispersed in a xylene solution, coated on an aluminum substrate, and its thermal stability was tested after drying and curing. The results showed that the coating still maintained structural integrity after being heated at 800°C for 30 minutes, and there were no obvious cracks or signs of decomposition on the surface; the thermal conductivity of the coating was significantly lower than that of traditional high-temperature coatings, and it had excellent thermal insulation properties. Through the above embodiments, the present invention verifies that the prepared APGs material has excellent thermal stability and application performance, breaks through the technical limitations of traditional alkyl glycosides in the high-temperature field, and provides new material solutions for high-temperature coatings, electronic packaging and other fields.
[0058] In summary, the alkyl polyglucoside material with high temperature stability and the preparation method thereof achieve the high polymerization degree and self-assembly of alkyl glycoside through a process combining enzyme-catalyzed reverse hydrolysis and glycosyl transfer. Different from the traditional APGs material, the present invention forms a cage-like nanostructure through molecular design and introduces π-π conjugation between molecules, thereby constructing a graphene-like hexagonal crystal system. This innovative structure effectively solves the problem that traditional APGs are easy to decompose and structurally unstable under high temperature conditions. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) tests show that the material still maintains structural integrity and functional stability in a high temperature environment of 580-930°C, and the decomposition loss is significantly lower than that of traditional biomaterials. In addition, the lightweight characteristics of the material give it significant advantages in high temperature applications, and it is particularly suitable for aerospace, electronic packaging, and high-temperature insulating coatings.
[0059] Moreover, by replacing the traditional high-temperature and high-pressure chemical synthesis method with a mild enzyme catalysis process, the use of harmful reagents is avoided, the risk of environmental pollution is reduced, and the selectivity of the reaction and the purity of the product are improved, which meets the requirements of sustainable development. Through X-ray diffraction and Raman spectroscopy characterization, it is found that the multilayer crystal structure in the material effectively improves its mechanical strength, overcomes the defects of the traditional APGs material with loose structure and insufficient performance, so that the material of the present invention still has stable physical and chemical properties under extreme conditions, significantly broadens its application field, and solves the problems of the existing alkyl polyglucosides in high temperature environment, such as insufficient thermal stability, poor mechanical properties and limited application range.
[0060] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0061] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an alkyl polyglucoside material with high temperature stability, characterized in that: The following steps are involved: S1. Glycosylation reaction: prepare a glucose solution with a concentration of 0.5M to 2.0M, mix it with an equal volume of sodium phosphate buffer, then add 1.0mL to 3.0mL of a hydrophobic alcohol compound, stir well to form a uniform mixture, add a catalyst, and then add 0.01M to 0.05M cobalt chloride and 0.01M to 0.05M copper sulfate to preliminarily generate an alkyl glycoside monomer; S2. Polymerization and self-assembly: The enzyme-catalyzed glycosyl transfer reaction further polymerizes the alkyl glycoside monomers to form a molecular structure in which the polysaccharide chain is combined with the alkyl chain. As the reaction proceeds, the molecules self-assemble under the action of the hydrophobic phase to form a nanoscale polymer framework with a cage-like structure. S3, reaction termination and separation and purification: after the reaction is completed, 3 mL of methanol is added to terminate the enzyme catalytic reaction, and then the enzyme catalyst is removed by using a filter membrane, and the excess reaction solvent is removed by vacuum evaporation, and then three times the volume of methanol is added and stirred and filtered to remove unreacted glucose, and finally the reaction solution is separated from 10 times the volume of ethanol-hexane mixed solvent by liquid-liquid separation, the organic phase is recovered, and the solvent is removed by rotary evaporation to obtain the purified polymerized alkyl polyglucoside; S4. Characterization of structure and performance: Infrared spectroscopy was used to detect the vibration peaks of the COC glycosidic bond and the alkyl chain. Nuclear magnetic resonance was used to determine the degree of polymerization and structural integrity of the material. The crystal structure of the material was further analyzed by X-ray diffraction and Raman spectroscopy to confirm the formation of a hexagonal crystal system with π-π conjugation. Thermal stability tests were performed using thermogravimetric analysis and differential scanning calorimetry. The results showed that the material can still maintain a stable structure and performance in a high temperature environment of 580–930°C.
2. The method for preparing an alkyl polyglucoside material with high temperature stability according to claim 1, characterized in that: The glycosylation reaction in S1 is carried out at 50°C-120°C.
3. The method for preparing an alkyl polyglucoside material with high temperature stability according to claim 1, characterized in that: The duration of the glycosylation reaction in S1 is 60-240 hours.
4. The method for preparing an alkyl polyglucoside material with high temperature stability according to claim 1, characterized in that: The hydrophobic alcohol compound in S1 is one of butanol, hexanol or octanol.
5. The method for preparing an alkyl polyglucoside material with high temperature stability according to claim 1, characterized in that: The catalyst in S1 is 24 U of α-glucosidase.
6. The method for preparing an alkyl polyglucoside material with high temperature stability according to claim 1, characterized in that: The pH value of the sodium phosphate buffer is 6.5-7.
5.
7. The method for preparing an alkyl polyglucoside material with high temperature stability according to claim 1, characterized in that: The volume ratio of ethanol to hexane in the S3 ethanol-hexane mixed solvent is 1:
1.
8. The method for preparing an alkyl polyglucoside material with high temperature stability according to claim 1, characterized in that: The pore size of the filter membrane in S3 is 0.22 μm.
9. An alkyl polyglucoside material with high temperature stability, characterized in that: The alkyl polyglucoside material is prepared by the preparation method of an alkyl polyglucoside material with high temperature stability as described in any one of claims 1 to 8.